2016
DOI: 10.1038/srep29525
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Degrades the Host Glycocalyx Leading to Altered Infection and Glycan Remodeling

Abstract: Complex glycans cover the gut epithelial surface to protect the cell from the environment. Invasive pathogens must breach the glycan layer before initiating infection. While glycan degradation is crucial for infection, this process is inadequately understood. Salmonella contains 47 glycosyl hydrolases (GHs) that may degrade the glycan. We hypothesized that keystone genes from the entire GH complement of Salmonella are required to degrade glycans to change infection. This study determined that GHs recognize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
77
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 54 publications
3
77
0
Order By: Relevance
“…and other foodborne pathogens. These seven sialidase and one sialic acid transporter mutant strain were constructed in the Weimer Laboratory (UC Davis, Davis, CA, USA) (6) as described by Datsenko and Wanner (7). Cultures were grown on 1.5% Luria–Bertani agar (Difco, Franklin Lakes, NJ, USA), with 10 µg/mL of chloramphenicol at 37°C, and then lysed (8).…”
Section: Genome Announcementmentioning
confidence: 99%
“…and other foodborne pathogens. These seven sialidase and one sialic acid transporter mutant strain were constructed in the Weimer Laboratory (UC Davis, Davis, CA, USA) (6) as described by Datsenko and Wanner (7). Cultures were grown on 1.5% Luria–Bertani agar (Difco, Franklin Lakes, NJ, USA), with 10 µg/mL of chloramphenicol at 37°C, and then lysed (8).…”
Section: Genome Announcementmentioning
confidence: 99%
“…Commensal and pathogenic microbes often take advantage of host-glycan abundance and importance by targeting them for the purposes of nutrition, cell attachment, invasion, and/or immunomodulation [2]. Many of the best-studied examples of the relationship between microbial glycan processing and the host-microbe interaction relate to intestinal microbes that degrade ingested and/or host-derived glycans [2][3][4][5][6][7]; however, other body sites that are rich in carbohydrates are also targeted by microbes, such as the oral cavity [8,9], genitourinary tract [10], and respiratory system [11]. The majority of respiratory pathogens appears to be relatively restricted in their carbohydrate usage, but Streptococcus pneumoniae stands out by its Abbreviations angle X-ray scattering; SBP, solute binding protein; STM, signature-tagged mutagenesis; UGL, unsaturated glucuronyl hydrolase; Xyl, xylose; GlcA, unsaturated D-glucuronic acid.…”
mentioning
confidence: 99%
“…That group also demonstrated that each of the four mutant amylase strains (Δ malS, Δ amyA, Δ glgX , and Δ glgB mutants) had different invasion phenotypes during the in vitro infection of differentiated colonic epithelial cells (Caco-2) (1); however, only the Δ malS mutant significantly ( P < 0.05) reduced adhesion and invasion during infection that were comparable to those seen with a nonpathogenic Salmonella strain (1). …”
Section: Genome Announcementmentioning
confidence: 95%